Weight change in patients followed in a dyslipidemia outpatient clinic - Dias, Patrícia (2005)
Objective: To evaluate the evolution of body weight in patients followed in a dyslipidaemia outpatient clinic.Methods: We randomly selected a sample of 143 patients followed in our dyslipidaemia outpatient clinic and registered their initial weight, at 3 and 6 months and after 1,3 and 5 years of follow-up. A subgroup of patients was prescribed a quantified caloric restriction diet and data from this group was analysed separately. We compared the mean weights of the total sample obtained at the different evaluation periods and also for each quartile of BMI; the lipid profile was compared at times 0 and 3 months.Results: Considering the whole sample, there was no significant weight variation at any interval considered. In the analysis by BMI quartiles, there was a statistically significant reduction from 3 to 6 months (p=0.014) for the 4th quartile and a borderline significant reduction from 0 to 6 months for the 3rd quartile (p=0.05).In the first 3 months there was a statistically significant reduction of the total and LDL cholesterol and triglycerides. In the subgroup with individually adapted caloric restriction (n=8) there was, during the 1st 3 months, a weight reduction of 2.18 Kg (p=0.033); in the same period, there was no statistically significant variation of the lipid profile, probably due to the reduced sample size.Conclusion: The caloric restriction diet appears to be more effective in weight reduction than the usual lifestyle changes, which, in turn, have a favourable effect in the lipid profile, at least in the short term